Prevalensi Dismenore pada Remaja Putri di Madrasah Aliyah Darul Ulum dan Miftahul Jannah Palangka Raya - Aida Kusnaningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Dysmenorrhea is pain before or during menstruation, occurring on the first day to several days of menstruation. This condition results in young women having difficulty concentrating while studying and absent in the teaching and learning process in class. The research design is quantitative descriptive research. The sample of the study were 160 female students in Madrasah Aliyah Darul Ulum and Miftahul Jannah Palangka Raya, with a purposive sampling technique. The questionnaire used was a question/statement containing the age of menarche, the incidence of dysmenorrhea, family history of menstrual pain. Data were analyzed univariately by frequency distribution test. The study found results from 160 respondents found the average age of menarche is 12.89 years with a standard deviation of 1.24, the lowest age of menarche is 9 years, and the highest is 17 years, has a history of dysmenorrhea in a family of 110 people (69%), and has menstrual pain 138 people (86%). This study concluded that the majority of respondents experienced menstrual pain, and had a family history of dysmenorrhea, and the age range of menarche 9-17 years with an average of 12.89 years.